Pharmacological prevention of renal ischemia–reperfusion injury in a rat model. Issue 3 (24th November 2021) - Deng, Yi; Li, Rachel W.; Yang, Yong Liang; Weiss, Steven; Smith, Paul N.
Abstract: Introduction: Renal ischemia–reperfusion injury (IRI) can lead to significant morbidity and mortality. It remains a leading cause of acute kidney injury and is therefore an important issue in trauma and renal transplant surgery. Various pharmaceutical agents have been used in an attempt to dampen the harmful effects of IRI but few have been shown to be useful clinically. Riluzole, Lidocaine and Lamotrigine have been demonstrated to show anti‐ischaemic properties in other organs; however, their use has not been tested in the kidneys. We investigated Riluzole, Lidocaine and Lamotrigine for their preventive effects of renal IRI using a rat model. Methods: Winstar rats ( n = 48) were divided into four groups ( n = 12 per group)—three treatment groups and one control group. Riluzole, Lidocaine and Lamotrigine were given prior to renal ischemia only (IO) or IRI. The degree of ischemia was measured by glutathione levels and a TUNEL assay was used to measure DNA fragmentation. Results: Riluzole, Lidocaine and Lamotrigine pre‐treatment each resulted in statistically higher glutathione levels compared to controls ( P = 0.002; P = 0.007 and P = 0.005, respectively). Riluzole and Lidocaine were also effective at preventing depletion of glutathione following IO ( P = 0.007 and P = 0.014 respectively), while Lamotrigine was ineffective in IO ( P = 0.71). The degree of DNA fragmentation seen on the TUNEL assay was markedly reduced in all three‐drug groups in both IO and IRI. Discussion: Riluzole, Lidocaine and Lamotrigine all have anti‐ischaemic effects in the rat kidney and can have potential therapeutic implications. Abstract :